ALKALI DIFFUSION IN PLAGIOCLASE FELDSPAR - Giletti B.J.; Shanahan T.M. (My University, 1997)
Tracer diffusion kinetics at 1 atm pressure under 'dry' conditions using 6Li, 41K, and 87Rb in four plagioclase feldspars have been determined. Diffusion profiles were measured using an ion microprobe (SIMS). The Arrhenius parameters and +/- 2σ uncertainties for Li, K, and Rb, respectively, in albite, are: pre-exponential factor (log D0) = -3.8 +/- 1.0; -3.4 +/- 1.4; and -5.8 +/- 3.8 (in m2/s) and activation energies = 146 +/- 14; 296 +/- 30; and 283 +/- 85 kJ/mol.The diffusion rate of K in albite at 700°C and 100 MPa water pressure equals that at 1 atm 'dry', suggesting that diffusion of K is not dependent on water fugacity between ~ 0.004 and 100 MPa. The K diffusion rate depends on plagioclase anorthite content and is approximately 20 times slower in labradorite than albite. Li diffusion rates in albite and anorthite are identical. A linear relation between log D for the alkalis measured and their ionic radius squared, permits an estimate of Cs diffusion kinetics. Diffusion rates are isotropic or nearly so in albite.
Keywords: DIFFUSION; ALKALIS; PLAGIOCLASE; ARRHENIUS RELATIONS; ALBITE